The effect of dietary supplementation with natural antioxidants on growth performance, antioxidant capacity and intestinal microbial counts of broiler - Gumus, R; Ercan, N; Özbilgin, A; Moğulkoç, MN; İmik, H (Journal of the Hellenic Veterinary Medical Society, 2024)
This study was carried out to determine the effects of different doses of curcumin and resveratrol added to the diet of broilers on growth performance, antioxidant metabolism and intestinal microflora. A total of 200 male broilers at the age of 0 days were used in the study. Groups of the study was designed in 5 groups as Control (CONT), CRM250, CRM500, RSV250 and RSV500, and 0, 250 mg kg-1 curcumin, 500 mg kg-1 curcumin, 250 mg kg-1 resveratrol and 500 mg kg-1 resveratrol were added to diets of the groups, respectively. Body weight (BW), average daily weight gain (DWG) and feed conversion ratio (FCR) values were found to be statistically similar in all groups (P > 0.05) at the end of the study. Feed consumption (FI) values are decreased in the CRM250 and CRM500 groups 28-35 between days, the CRM500 group in 0-42 between days (P < 0.05). It was determined that glutathione peroxidase (GPx) activity in serum was significantly increased in the CRM250 group (P < 0.05), and superoxide dismutase (SOD) activity in thigh tissue was significantly increased in the CRM500 group (P < 0.01). Escherichia coli (E. coli) colonization in the intestinal flora was significantly reduced in the RSV500 group (P < 0.01). As a result, according to the findings obtained, it was seen that the additives applied did not have a negative effect on performance parameters, also had curative effects on antioxidant metabolism and intestinal microflora.